Upper limb function and functional independence in patients with shoulder pain after stroke - Nickel, Renato; Lange, Marcos; Stoffel, Diane Priscila; Navarro, Elaine Janeczko; Zetola, Viviane F (Arquivos de Neuro-Psiquiatria, 2017)
To examine the frequency of shoulder pain following stroke.Stroke patient function was evaluated using the Functional Independence Measure (FIM) and Scale for Upper Limb Function in Stroke (SULFS). Function scores were examined and compared between the shoulder pain group (SPG) and the no shoulder pain group (No-SPG).A total of 58 patients, 22 women (37.9%), were included in this study. The mean patient age was 49.2±10.8 years and study evaluations were done 3.52±2.26 months after stroke. A total of 16 patients (27.6%) were in the SPG and 42 patients (72.4%) were in the No-SPG. The SPG scored significantly lower on the FIM (SPG: 91.06±14.65 vs. No-SPG 114.62 ± 2.27; p < 0.01) and SULFS (SPG median: 2 [range: 1-4], No-SPG median: 5 [range: 1-5]; p < 0.01) than the No-SPG.Shoulder pain commonly occurs after stroke and is related to the affected upper limb function and functional independence in stroke patients.
Keywords: stroke; shoulder pain; rehabilitation; activities of daily living